Pengaruh Permainan Konstruktif Tangram terhadap Berfikir Kreatif pada Siswa Sekolah Dasar - Jenny Nugraheni Irawan; Aditya Nanda Priyatama; Afia Fitriani (JIP (Jurnal Intervensi Psikologi), 2020)
Tangram constructive game is one of the games that can be used to train creative thinking. The purpose of this study was to know the effect of tangram constructive game on creative thinking in elementary school student. The hypithesis of this study is that there is a significant effect of tangram constructive game on creative thinking before and after intervention. This research is an experimental study with nonequivalent crontrol group design. Data collection uses figural creativity test. Data analysis used the Mann-Withney technique with the SPSS statistical program. The result of the study show that the value of Z count = -2,363 with p = 0,18 (p<0,05). So, if can be concluded that there is a significant effect on creative thinking after intervention.